PENEGAKAN HUKUM TERHADAP PELAKSANAAN PAJAK PARKIR DI KABUPATEN PELALAWAN - Bagio Kadaryanto; Andrew Shandy Utama (Ensiklopedia Social Review, 2020)
One of the potential Regional Taxes to increase Local Revenue in Pelalawan Regency is the Parking Tax. Parking Tax is a tax on the operation of a parking space outside a body of a road, whether provided in connection with the principal of the business or that is provided as a business, including the provision of motorized vehicle day care. This research aims to explain the law enforcement of the implementation of the Parking Tax in Pelalawan Regency based on Pelalawan District Regulation Number 1 of 2011 concerning Regional Taxes. The method used in this research is socio-legal research. Parking Tax Implementation in Pelalawan Regency has not run optimally because in 2017 it is known that the Ramayana Pangkalan Kerinci and Kerinci Business Center do not deposit Parking Taxes. The efforts made by the Pelalawan Regency Financial and Asset Management Agency to maximize Local Tax revenue are forming a Regional Tax Control and Billing Task Force. Article 130 of Pelalawan District Regulation Number 1 of 2011 concerning Regional Taxes stipulates that a sanction of 400% (four hundred percent) of the principal tax payable will be imposed if any taxpayer who deliberately does not deposit the collected tax will cause losses on regional finance.